Security of person and citizen: some issues of legal ensuring in Kazakhstan (International relations and international law Journal, 2016)
The object of this article is to study the current state of defense of rights and interests of citizens in relation to the Republic of Kazakhstan. On the basis of a comparative, systematic and presumptive methods of analysis and synthesis author shows problems and gaps of its legal support offering some concrete steps to their solution and supplement. Particular attention is paid to the necessity of reforming the national legal system and law enforcement in the context of the Commission on Human Rights under the President of the Republic of Kazakhstan and the plenipotentiary for Human Rights. There are revealed significant shortcomings and deficiencies in the functioning of the latter institution (Ombudsman) in Kazakhstan, including the absence of a special law regulating the status, full autonomy and independence in decision making, a vulnerable legal position in comparison with the same position in European countries. Emphasized the fact that the Human Rights Commission under the President should not have the authority to direct defense of human rights and fundamental freedoms.
Keywords: security; human and citizen rights; ensuring; Kazakhstan